Knowledge and practice on pressure ulcer wound care among nurses working in the Philippines - Ramirez, Ma. Elena A.; Paredes, Chris N.; Reyes, Justine Ericca A.; Reyes, Leigh Nicole T.; Rivero, Christelle Danielle T.; Rocamora, Jessamyn E.; Simoy, Danessa C. (Manila College of Nursing University of the Philippines, 2017)
Background. For every 1,000,000 patients who developed pressure ulcer, 65,000 died from its complications (Agency for Healthcare Research Quality, 2008). Nurses play a key role in the management of pressure ulcer as they perform the assessment, cleaning, and dressing of wounds preventing such complications from occurring. The quality of wound care is highly dependent on the knowledge of nurses which is influenced by several factors. Their practice is also influenced by knowledge and other factors in their working environment. Thus, this study aims to determine the knowledge of nurses as well as its relationship with highest educational attainment, area of experience, years of experience, area of experience and formal trainings attended. Also, this study aims to describe the practice of nurses and determine its relationship with their working environment, namely staffing conditions, policies and guidelines and availability of supplies.

Methodology. This study used a descriptive correlational design wherein an online survey, Survey Monkey, was utilized. Convenience sampling was used in order to gather data from registered nurses who are currently working in the Philippines. An 82-item web-based survey was administered. Publication materials were posted in different social networking sites to gather responses.

Results. There were two hundred twenty-two eligible respondents (N=222) who answered the survey. Majority (n=122, 54.95%) had moderate knowledge. Respondents scored higher on staging (x=7.09, SD=1.46) compared to wound description (x=5.35, SD=1.39). In addition, it was also found out that nurses who worked for less that 10 years were more knowledgeable compared to those who worked for more than 10 years.

Majority of the respondents (58.11%) practice wound care. In assessing, majority of them (n=78, 60.47%) are adherent to wound assessment practices based from the recommendations of the NPUAP/EPUAP/PPPIA Guidelines. The Braden Scale for Predicting Pressure Ulcer Risk was the most used assessment tool (77.01%). In wound cleaning and dressing, clean gloves were used by most of the respondents for cleaning pressure ulcer (65.1%) and for removing previous dressing (90.7%) while sterile gloves were mostly used for applying dressing (55.8%). The respondents always used saline solution (62.79%) in cleaning while they most often used systematic pain medications in pain reduction (32.56%).

There was an association between knowledge and years of experience (p-value=0.02). There was a weak correlation between the practice of nurses and staffing conditions (r=0.255, N=129, p<0.01), as well as with availability of supplies (r=0.238, N=129, p<0.01). Also, it was found out that practice and policies and guidelines had moderate association (=0.516). Overall, there was sufficient proof to generalize that the working environments were significantly related to practice of nurses.

Conclusion. It was found that except for years of experience there is no sufficient proof to prove that educational attainment, area of work experience, and formal training attended are significantly related to the knowledge of nurses in pressure ulcer wound care. However, there was sufficient proof to generalize that the working environments was significantly related to practices. Thus, skill alone does not determine the nurse’s practice in performing pressure ulcer wound care. Rather, factors in the environment may affect the type of care provided in patients with pressure ulcers.

Recommendations. Based on the results of the study , the researchers recommend for health institutions to consider improving staffing conditions, ensuring availability of supplies, and implementing policies and guidelines to improve the outcomes of pressure ulcer wound care. Also, nurses should continue to pursue further education, seek for more experience, and update their knowledge through evidence- based guidelines and studies to provide efficient pressure ulcer wound care.
Research (In partial fulfillment of the requirements of the course N121.1: Intensive Nursing Experience, Hospital-based) -- University of the Philippines Manila, June 2017.
Keywords: Intensive nursing experienced -- Hospital-based.